Draft Genome Sequences of Helcococcus ovis Strains Isolated at Time of Metritis Diagnosis from the Uterus of Holstein Dairy Cows - Cunha, Federico (Microbiol Resour Announc, 2019)
Helcococcus ovis is an emerging pathogen implicated in the pathogenesis of metritis in dairy cows. Herein, we report the first draft genome sequences of four Helcococcus ovis isolates from the uterus of dairy cows with metritis. This information will enable a better understanding of the bacterium’s pathogenicity and antimicrobial resistance.